Eventos extremos na Amazônia: avaliação da seca de 2005 e 2010 na bacia hidrográfica do rio Solimões - SERRÃO, Edivaldo Afonso de Oliveira (2019)
The basin of the Solimões river has its water recharge modulated by various weather systems, where the northern part suffers greater influence of Intertropical Convergence Zone (ITCZ) and the southern portion influences the convergence zone of the (SACZ) south Atlantic and convective clusters and frontal systems operating in this region. However events of El Nino and the Atlantic Dipole can modulate the rainfalls causing severe droughts. The objective of this study was to analyze the rainfall behavior in the basin of the Solimões River in 2005 and 2010, marked the worst droughts of the century in Amazônia. The results showed that the rainfall in the Solimões basin has been drastically reduced in the southwest region in 2005. In 2010 the entire western and southern portion of the basin were affected during drought. This behavior is linked occurrence of ENSO phenomena positive phase and the positive dipole Atlantic, which are strong modulators of precipitation in the Amazon. Therefore, it is observed that the Solimões river has suffered from the weather phenomena that operate in the Amazon region, with consequent impact on the cities that are located on its banks.